Transformative Guidance and Counseling Management in Islamic Education Practice - Dedi Junaedi; Siti Fatimah; M Rezza Septian; Sahliah Sahliah; Tamtam Kamaluddin (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Guidance and Counseling (BK) services play a crucial role in transformative education, but are often hampered by a secular paradigm that neglects the spiritual dimension of students. This study aims to formulate a systematic, transformative BK management model based on Islamic values. Using qualitative case study methods and inductive data analysis, a results-oriented, data-driven managerial framework was developed. The results emphasize that BK must go through the P-O-A-C stages integrated with Islamic values, supported by strong collaboration between stakeholders, and implement digital innovation to overcome implementation challenges and achieve the development of Perfect Humans in the digital era.